The Influence of TikTok Hidden-Gem Culinary Reviews on Brand Attitude and Purchase Intention - Debby Kania Bustami; Siska Noviaristanti (Jurnal Administrasi Bisnis, 2026)
This study examines the influence of emotional appeal, influencer attractiveness, influencer trustworthiness, and influencer expertise on consumers’ attitudes toward brands and purchase intentions among TikTok users in Indonesia, grounded in the Source Credibility Theory framework. The research focuses on “hidden gem” culinary review content. Data were collected through an online questionnaire using a five-point Likert scale from 239 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The measurement model confirms satisfactory reliability and validity across all constructs. All five hypotheses are empirically supported. Attitude toward the brand is found to be the strongest predictor of purchase intention (β = 0.696) and serves as a central mediator between influencer credibility and consumers’ behavioral intentions. Emotional appeal exhibits the strongest effect on brand attitude (β = 0.335), followed by trustworthiness (β = 0.302), attractiveness (β = 0.237), and influencer expertise (β = 0.203). These findings extend the application of Source Credibility Theory to a relatively underexplored context and provide practical guidance for culinary businesses in designing more effective influencer marketing collaborations.